Role of Aspect and Soil on the Structure and Composition of Quercus floribunda Natural Stands in Garhwal Himalaya - Dhanai, C. S.; Panwar, Vijender P. (Indian Forester, 1999)
The impact of aspect, altitude, slope and soil has been studied on the moist temperate forest of Quercus floribunda in Garhwal Himalaya. Four faces namely North-West, South-East and South-West have been studied to understand the growth behaviour of Q. Floribunda with varying altitudes. The total basal cover was found highest (4347.33 cm2/100m2) on the North-West facing slope. The Q. Floribunda was found associated with Rhododendron arboreum as a main companion species on all the faces. The soil of Q. floribunda forest on various aspects has moderate soil pH, where maximum amount of potassium (800 kg ha-1) and phosphorous (29.59 kg ha-1 ) was observed on North-West aspect, which has supported the growth of Q. floribunda forests on these aspects. Dominance of Q. floribunda was recorded for resource utilizatiQn on North-West aspect for both trees and saplings, which indicates greater equitable share of resources among the various species present on this aspect. It is recommended that the plantations of Q. floribunda should be done on North facing aspects for optimum yield and sustainable development.